NUMERICAL STUDY OF THE GEOMETRIC INFLUENCE OF A FIN IN A CYLINDRICAL HEAT EXCHANGER FOR MELTING OF PCM - Spengler, F. C.; Oliveira, B.; Oliveski, R. C.; Rocha, L. A. O. (Revista de Engenharia Térmica, 2019)
The thermal heat storage it’s an effective way to suit the energy availability with the demand schedule. It can be stored in the means of sensible or latent heat, the latter applying a material denominated Phase Change Material (PCM), which is provided as organic compounds, hydrated salts, paraffins, among others. The latent heat storage systems offer several advantages, like the practically isothermal process of loading and unloading and the high energy density. However, the low thermal conductivity makes the cycle prolonged on these systems, restricting its applicability. Applying computational fluid dynamics, the behavior of the PCM melting process was studied in cylindrical cavities with horizontal and vertical fins, aiming the optimization of the fin geometry. In this way the fin area was kept constant, varying its aspect ratio. The numerical model was validated with results from the literature and it’s composed of the continuity, momentum and energy equations increased by the phase change model. Qualitative and quantitative results are presented, referring to mesh independence, contours of velocity, net fraction and temperature at different moments of the process. The results of the study indicate that the position of the fin in the heat exchanger influences the melting process, although the vertical fins have a faster total melting process, horizontal fins can reach larger partial liquid fractions in less time in the heat exchanger. Such as the position of the fin, the increase of its length propitiates the reduction of the melting time, evidencing the optimal aspect ratio.